Play It Again With Feeling: Computer Feedback in Musical Communication of Emotions. - Juslin, Patrik N.; Karlsson, Jessika; Lindström, Erik (Journal of Experimental Psychology. Applied, 2006)
Communication of emotions is of crucial importance in music performance. Yet research has suggested that this skill is neglected in music education. This article presents and evaluates a computer program that automatically analyzes music performances and provides feedback to musicians in order to enhance their communication of emotions. Thirty-six semi-professional jazz/rock guitar players were randomly assigned to one of 3 conditions: (1) feedback from the computer program, (2) feedback from music teachers, and (3) repetition without feedback. Performance measures revealed the greatest improvement in communication accuracy for the computer program, but usability measures indicated that certain aspects of the program could be improved. Implications for music education are discussed. Reprinted by permission of the publisher.